Pattern formation in the Drosophila wing: the development of the veins. - de Celis, J.F. (BioEssays, 2003)
The veins are cuticular structures that differentiate in precise patterns in insect wings. The genetic and molecular basis of vein pattern formation in Drosophila melanogaster is beginning to be unravelled with the identification and characterisation of the gene products that position the veins and direct their differentiation. Genes affecting the veins fall into two groups: transcriptional regulators that specify individual veins, and members of signalling pathways involved in patterning and differentiation of the veins. The elaboration of the vein pattern is progressive in time and requires the coordinated activities of these signalling pathways and the transcription factors regulated by them. Although the network of genetic interactions that determine vein cell fate is well understood, very little is known about the cellular biology underlying the acquisition of vein histotype.